Clinical Characteristics of Patients Underwent Frozen Section Biopsy of Ovarian Masses in BSMMU, Dhaka, Bangladesh - Sultana, Ismat; Akhter, Salma; Begum, Shamim Ara; Begum, Syeda Humaira; Haque, Mohammad Azizul; Begum, Ayesha (IAHS Medical Journal, 2022)
Background: Women with suspected early-stage ovarian cancer need surgical staging which involves taking samples from areas within the abdominal cavity and retroperitoneal lymph nodes in order to inform further treatment. Frozen section is an important and helpful adjunct in the intraoperative diagnosis of ovarian tumors. The aim of the study was to evaluate the clinical characteristics of patients undergoing frozen section biopsy in the diagnosis of ovarian malignancies. Materials and methods: This prospective observational study included 30 cases of ovarian masses from the Department of Obstetrics and Gynecology, Bangabandhu Sheikh Mujib Medical University (BSMMU) from March 2014 to August 2014. Clinical feature, sonographic evaluation, CA-125, CA-19-9 and frozen section biopsy report were collected. Results: The mean age was 35.6±12.4 years with range from 14 to 70 years. Frozen section biopsy was true positive in 6 cases and no false positive, 1 false negative and true negative in 23 cases compared to histopathology. Frozen section biopsy has sensitivity, specificity, accuracy, positive predictive and negative predictive values were respectively, 85.7%, 100.0%, 96.7%, 100.0% and 95.8% in evaluation of ovarian masses. Conclusion: The histopathological diagnosis of the present study significantly correlated well with frozen section biopsy findings and the validity tests are almost identical as observed by many investigators. IAHS Medical Journal Vol 4(2), December 2021; 32-35